Zyxin regulates embryonic stem cell fate by modulating mechanical and biochemical signaling interface - Zhang, Songjing (2023)
Biochemical signaling and mechano-transduction are both critical in regulating stem cell fate. How crosstalk between mechanical and biochemical cues influences embryonic development, however, is not extensively investigated. Using a comparative study of focal adhesion constituents between mouse embryonic stem cell (mESC) and their differentiated counterparts, we find while zyxin is lowly expressed in mESCs, its levels increase dramatically during early differentiation. Interestingly, overexpression of zyxin in mESCs suppresses Oct4 and Nanog. Using an integrative biochemical and biophysical approach, we demonstrate involvement of zyxin in regulating pluripotency through actin stress fibres and focal adhesions which are known to modulate cellular traction stress and facilitate substrate rigidity-sensing. YAP signaling is identified as an important biochemical effector of zyxin-induced mechanotransduction. These results provide insights into the role of zyxin in the integration of mechanical and biochemical cues for the regulation of embryonic stem cell fate.